Lactate Flux and Gluconeogenesis in a Fasted, Weaned Northern Elephant Seal Weanling (Mirounga Angustirostris) - Tavoni, Stephen K. (Sonoma State University, 2012)
During prolonged fasting, an animal will derive its metabolic needs from the `catabolism of fat as well as amino acids from lean tissue. Certain organs though are glucose dependent and require a steady supply of carbohydrates. To reduce the degradation of lean protein and oxidation of glucose by peripheral tissue, overall endogenous glucose production (EGP) is reduced across the fasting duration. Northern elephant seals (Mirounga angustirostris) on the contrary do not suppress glucose production even when burdened with the demands of development, lactation, or reproduction. We investigated the source of this EGP (Le. glucose recycling) through possible Cori cycle inputs by measuring the percentage of lactate gluconeogenesis (GNG) through a primed constant infusion of [U_ 14C] lactate and [63H] glucose. The rate of appearance (Ra) of lactate decreased significantly across the fasting duration, 4.60 ± 0 .66 to 3.47 ± 0.87 mmol'min-1, and had a direct impact on the Ra of glucose. Plasma lactate levels decreased across the fasting duration and caused an overall decrease in lactate gluconeogenesis (GNGlactate), suggesting an adaptation that is intended to spare protein and prolong fasting. Insulin decreased over the fasting duration and was directly tied to both glucose and lactate production. The inefficiency of glucose recycling could be a possible adaptation to guard against ketoacidosis and hypoxia/ischemia while on land or while diving . . With their hyperglycemic metabolism and little known side effects, these animals are a special diabetic model in which future research could shed insight into overall mammalian energy dynamics. Tavoni, Stephen K. 2012. Lactate Flux and Gluconeogenesis in a Fasted, Weaned Northern Elephant Seal Weanling (Mirounga Angustirostris). Department of Biology, Sonoma State University.